(untitled) (Географический вестник=Geographical bulletin, 2017)
В статье приведены характеристики энотуризма («винного туризма») как разновидности туристской аттрактивности сельских территорий. При этом подчеркиваются его мультипликативный эффект, культурное значение, тесная связь с гастрономией и другими элементами региональной и локальной культуры. ETHNOTOURISM AS FACTOR FOR REGIONAL AND LOCAL DEVELOPMENT The paper presents the characteristics of enoturizm ("wine tourism") as a kind of tourist attractiveness of rural areas, with its multiplier effect highlights the cultural importance, a close connection with gastronomy and other elements of regional and local culture.